2017
DOI: 10.3390/insects8030100
|View full text |Cite
|
Sign up to set email alerts
|

Lipase Activity in the Larval Midgut of Rhynchophorus palmarum: Biochemical Characterization and the Effects of Reducing Agents

Abstract: Lipases have key roles in insect lipid acquisition, storage, and mobilization and are also fundamental to many physiological processes in insects. Lipids are an important component of insect diets, where they are hydrolyzed in the midgut lumen, absorbed, and used for the synthesis of complex lipids. The South American palm weevil Rhynchophorus palmarum is one of the most important pests on commercial palm plantations. However, there are few studies about lipid digestion for this insect. In this work, we have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
4
22
0
Order By: Relevance
“…Similar results were shown for other insects; [38] and Santana et al [41] showed that the activity of lipase from R . prolixus and Rhynchophorus palmarum increased by increasing calcium ion concentrations respectively.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar results were shown for other insects; [38] and Santana et al [41] showed that the activity of lipase from R . prolixus and Rhynchophorus palmarum increased by increasing calcium ion concentrations respectively.…”
Section: Discussionsupporting
confidence: 86%
“…High temperature may interfere with hydrogen bond of enzyme causing denaturation of this enzyme [32]. Similar results have been shown in other insect lipases, as in gypsy moth Lymantria dispar [40], Rhynchophorus palmarum [41] and N . aenescens [16].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…High temperature may interfere with the hydrogen bond of enzyme causing denaturation of this enzyme (Zeng and Cohen, 2000a). Parallel results have been revealed in other insect lipases, as in gypsy moth Lymantria dispar (Mrdaković et al 2008), Rhynchophorus palmarum (Santana et al 2017) and N. aenescens (Zibaee, 2012). In contrast, some invertebrates showed the highest activity of lipase at 60°C such as the Mediterranean green crab Carcinus mediterraneus (Cherif et al, 2007) and the Antarctic krill Euphasia superba (Barriga González, 2006).…”
Section: Discussionmentioning
confidence: 66%